Predicting independent walking ability using the Simpliﬁed Stroke Rehabilitation Assessment of Movement, Berg Balance Scale, and Barthel Index for Activities of Daily Living in individuals post-stroke: an observational preliminary study - Romanyshyn, Mykola (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The purpose of this study was to determine cut scores to predict independent ambulation for the Simpliﬁed Stroke Rehabilitation Assessment of Movement (S-STREAM), Berg Balance Scale (BBS), Barthel Index (BI) for Activities of Daily Living for patients with time after stroke up to 1 year. The study’s second goal was to establish statistical dependence between the tests the S-STREAM, BBS, BI, and the Functional Ambulation Category (FAC).Methods. Cohort observational retrospective pilot study by design. Twenty-four people who suﬀered a stroke within the past year were enrolled in the study. The FAC was used to classify patients into independent walking and non-walking groups (scores 0–2 are non-walking patients, scores 4–5 are independent walking patients). Receiver operating characteristic (ROC) curve analysis was performed for the S-STREAM, BBS, BI selected according to the multiple logistic regression analysis with dichotomy on groups independent walking patients and not.Results. ROC analysis of scores at admission were used to determine cut scores for the independent waking ability for each of the listed measures. The cut score for S-STREAM was 19 points, for BBS was 27 points and for BI was 65 points. Based on this analysis it appears there is suﬃcient evidence to conclude a signiﬁcant linear relationship between all tests the S-STREAM, BBS, BI, and FAC. Conclusions. In patients who were ambulators, less than one year post stroke, this pilot study established a cut score for standardized assessment tools S-STREAM, BBS, BI for Activities of Daily Living.
Keywords: simpliﬁed stroke rehabilitation assessment of movement; Berg balance scale; Barthel index for activities of daily living; functional ambulation category